Rangeland Management and Ecological Adaptation Analysis Model for Astragalus curvirostris Boiss - Farhad Aghajanlou; Hamidreza Mirdavoudi; Mohammad Shojaee; Eileen Mac Sweeney; Andrea Mastinu; Parviz Moradi (Horticulturae, 2021)
The present study investigates the ecological requirements of Astragalus curvirostris Boiss, with emphasis on determining the ecological factors that affect the distribution of plant species, and the species’ response to changes in ecological factors using a Generalized Additive Model (GAM) in the Iranian Province of Zanjan from 2017 to 2019. Randomized-systematic sampling was used to collect vegetation data. Data analysis was performed using SPSS17 and CANOC4.5 software. The results showed that the growth and development of A. curvirostris change according to environmental factors linked to the composition of the soil and the variety of the other species present. This model is indicative of a competitive limitation along the environmental gradient. By understanding all environmental parameters, the necessary steps could be taken towards planning proper management programs, including rangeland grazing management and determining the proper moment for seed collection, which will result in the conservation, improvement, and restoration of rangelands.